The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/job.2549
|View full text |Cite
|
Sign up to set email alerts
|

What if my coworker builds a better LMX? The roles of envy and coworker pride for the relationships of LMX social comparison with learning and undermining

Abstract: Although the extant literature has demonstrated the benefits of building a higher leader-member exchange (LMX) relationship with a leader, it has overlooked the efforts by lower LMX employees to leverage the difference from higher LMX coworkers. Integrating social comparison theory and EASI theory, we contend that lower LMX social comparison (LMXSC) is associated with positive (self-improving) and negative (undermining) behavior via different emotional mechanisms and that the focal employee's perceptions of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 83 publications
0
24
0
Order By: Relevance
“…However, social comparison theory [ 8 ] indicates that employees are inclined to make social comparisons at the workplace and direct their attitudes and behaviors to their jobs [ 9 , 10 ]. Among them, the most likely is to make an upward comparison, that is, with people who perform better than themselves or those who obtain more resources [ 11 , 12 ]. As more and more modern organizations collaborate in teams, interaction and helping behaviors among colleagues are more common and comparable [ 7 ].…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, social comparison theory [ 8 ] indicates that employees are inclined to make social comparisons at the workplace and direct their attitudes and behaviors to their jobs [ 9 , 10 ]. Among them, the most likely is to make an upward comparison, that is, with people who perform better than themselves or those who obtain more resources [ 11 , 12 ]. As more and more modern organizations collaborate in teams, interaction and helping behaviors among colleagues are more common and comparable [ 7 ].…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Given the social context in which receiving help occurs [ 3 ], a pertinent question is whether the positive effect of receiving help will still exist when employees conduct upward social comparison. Many studies have found that upward social comparison can activate the emotion of envy [ 11 , 12 ], which is a negative emotion that individuals experience when they are in a disadvantageous position in resource competition. Therefore, this upward social comparison of received help may evoke envy, thus reducing their citizenship behaviors to preserve their advantages and resources.…”
Section: Introductionmentioning
confidence: 99%
“…In the upward social comparison, social rejection is a status threat-related response elicited by envy (Breidenthal et al, 2020). As a consequence of seeing other's superiority, individuals have negative feelings toward themselves: They feel stressed about getting behind and unable to achieve what others already have, and depressed about the perceived unfairness in the way good fortune is distributed (Dineen et al, 2017;Pan et al, 2021;Tussing et al, 2022). The rejector is not intended to take social rejection as deviant behavior but as a way of hiding or releasing the psychological burden caused by status threats in the social interaction.…”
Section: Mediating Effect Of Social Rejectionmentioning
confidence: 99%
“…We propose that social rejection is one way people prevent themselves from self-depletion while seeing others' goodness in the upward social comparison. Past research on upward social comparison is conducted in the social interaction context, where the comparer responds to such comparisons by prosocial and anti-social behaviors (Pan et al, 2021;Yang and Tang, 2021;Boecker et al, 2022). Our study investigates the situation where individuals take an avoidance attitude toward upward social comparison by denying participation via social rejection.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…In doing so, coworkers gradually recognize i-dealers' strengths and their own weaknesses, and get effective information on how to improve themselves (Ma et al, 2022), e.g., i-dealers' workflows, and risky negative behaviors (Lee and Duffy, 2019). Besides observation and imitation, coworkers can also directly interact with i-dealers, e.g., by seeking advice, and asking for feedback (Pan et al, 2021). Considering that i-dealers give coworkers more careful, accurate, and targeted feedback through interaction (Lee and Duffy, 2019), coworkers can receive more direct information input (De Stobbeleir et al, 2011) to gradually close the gap with i-dealers (Wang et al, 2021a).…”
Section: The Mediating Role Of Learningmentioning
confidence: 99%